If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + -4 = 8(n + 6) + 6(5n + -8) Reorder the terms: -4 + -3n = 8(n + 6) + 6(5n + -8) Reorder the terms: -4 + -3n = 8(6 + n) + 6(5n + -8) -4 + -3n = (6 * 8 + n * 8) + 6(5n + -8) -4 + -3n = (48 + 8n) + 6(5n + -8) Reorder the terms: -4 + -3n = 48 + 8n + 6(-8 + 5n) -4 + -3n = 48 + 8n + (-8 * 6 + 5n * 6) -4 + -3n = 48 + 8n + (-48 + 30n) Reorder the terms: -4 + -3n = 48 + -48 + 8n + 30n Combine like terms: 48 + -48 = 0 -4 + -3n = 0 + 8n + 30n -4 + -3n = 8n + 30n Combine like terms: 8n + 30n = 38n -4 + -3n = 38n Solving -4 + -3n = 38n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-38n' to each side of the equation. -4 + -3n + -38n = 38n + -38n Combine like terms: -3n + -38n = -41n -4 + -41n = 38n + -38n Combine like terms: 38n + -38n = 0 -4 + -41n = 0 Add '4' to each side of the equation. -4 + 4 + -41n = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -41n = 0 + 4 -41n = 0 + 4 Combine like terms: 0 + 4 = 4 -41n = 4 Divide each side by '-41'. n = -0.09756097561 Simplifying n = -0.09756097561
| 5x^2=22x+15 | | 6w+3(w-1)=17 | | -3(-4+4x)=-23-5x | | .5x-.75y=-2 | | 6x+7=4x+15 | | 3x+2(3x+3)=8x+4 | | 3(y-12)=2(4y+22) | | 5x+11=4x+17 | | -(6p-6)=-(1-p) | | 4x^2+11x-8=0 | | 6k-4(k+6)=-2 | | 8(-2+7m)=32+8m | | -(8-6a)-(32+5a)-1=-(4-7a)+(-a)+3 | | .5(x+5)-4=.33(2x-1) | | 2(9n-1)-(10+x)=35 | | 4(x-3)+(x-1)=28 | | 5(2m+3)-(1-2m)=2[3(3+2m)-3-m] | | 5/8+5/8= | | 6(2b+5)=-4b+52 | | 2(c+5)=90 | | 11x=15-4x | | 6(9a-3b)-8(2a+4b)=0 | | 2/5=x/3 | | -6(3-x)+1=3(x-3) | | 5-2x=66 | | 900x-200=500x+600 | | 3(x-4)=-x-4 | | 5m-8m+42=96 | | -4(6x+3)=-60 | | 5-2x=61 | | 10d-8=4d-20+2d | | x^3+5x^2-2x-10=0 |